Determination of Optimal Conditions for Retention of Sulfur Dioxide by Waste Ulexite Ore in an Aqueous Medium - Çopur, Mehmet; Karagoz, Ozlem; Kocakerim, M. Muhtar (Taylor & Francis Inc, 2017)
The main aim of this study was to remove sulfur dioxide (SO2), which is one of the most significant air pollutants emitted from thermal power stations, using waste ulexite ore, which cannot be recycled industrially and poses a risk for the environment. In experiments conducted at atmospheric pressure in an aqueous environment, the optimization of holding SO2 with waste ulexite ore has been investigated comprehensively and determined how much SO2 could be retained in solid waste. The Taguchi method was used to determine the optimal conditions, and the effectiveness of the parameters was identified by variance analysis. The selected parameters and their ranges were defined as temperature (293-333 K), solid to liquid ratio (0.4-0.6 g mL(-1)), particle size (150-600 mu m), time (10-30 min), pH (5.5-7.5), and stirring speed (350-800 rpm). The optimal conditions for these parameters were determined to be 333 K, 0.45 g mL(-1), 250 mu m, 15 min, pH 6, and 350 rpm, respectively. Among all the parameters, temperature and pH were found to be the most effective. The results of the study revealed that SO2 can be retained in solid waste with calcium content of the boron minerals as CaSO3 center dot 0.5H(2)O and nearly whole B2O3 in the waste ulexite passes into solution. Under the optimum conditions, 86% of B2O3 passed into the solution and 75.2 L SO2 was retained by 1 kg waste ulexite ore. Thus, both B2O3 recovery and SO2 removal were materialized, while waste ulexite ore was evaluated and removed, simultaneously.
Keywords: Boron minerals; Desulfurization; Optimization; SO2; Taguchi method; Ulexite